Digitization in Finance and Accounting: Accounting treatment of ERP and RPA systems using the example of SAP S4 / HANA at credit institutions - Stephan Danzer; Bernd Hacker (Technische Hochschule Rosenheim, 2021)
Technological advancement and digitization have become more and more important in recent years. This is particularly true for credit institutions. The core banking systems used for internal processes are therefore subject to increasing digital change. In many banks, outdated IT systems are still in use, which often lack the basic functionalities that are essential for innovations. In order to achieve a sufficient functionality of the information technology in the company, core banking systems are implemented, which achieve the mapping of almost all bank-specific processes. In addition, so-called software robots are used to automate standard processes with increasing frequency. Due to the lack of standard products in previous years, there is an abundance of in-house developments. While self-developed systems dominate in the European as well as North and South American markets, earlier in-house developments in the German-speaking countries have mainly been replaced by standardized core banking systems. The introduction of standard ERP systems poses a major challenge for financial institutions. Not only does the implementation effort in terms of financial resources and working time play an important role, but also the ongoing expenses for maintenance and further development. These investments not only secure and promote the ability to innovate in the age of digitization, but also create an asset in the company. The evaluation for the accounting representation is an increasing challenge due to the steadily increasing complexity of information processing technologies. Questions arise regarding the access assessment, the follow-up assessment and the handling of previous systems. In the following, accounting according to the international accounting standards for the implementation of the ERP system SAP S/4HANA in credit institutions is shown. The procedure and the results are not limited to banks, but can be applied analogously to many industries.
urn:nbn:de:bvb:861-opus4-18320
Keywords: 650; Digitization